Physical properties of materials - White, Mary Anne (Boca Raton, FL : CRC Press, 2012)
"The second edition of a best seller, this book introduces principles of materials science from the perspective of various properties optical, thermal, electrical, magnetic, and mechanical highlighting the relationships among the properties from an atomic approach. The book covers timeless principles along with exciting contemporary materials science concepts. Covering the breadth of materials science, it is ideal for a one-semester introductory class in materials chemistry or materials physics as well as for materials engineering interested in a molecular approach"--
"Materials science offers a wonderful opportunity to introduce students to basic principles of matter through forefront research topics, of immediate or near-future direct application to their lives. Materials research is advancing rapidly. New topics in this second edition include: materials and sustainability; carbon nanotubes; other nanomaterials including nanocomposites; quantum dots; spintronics; magnetoresistance. In addition, in response to comments from other professors who taught from the first edition, this new edition includes and an introductory section on structures of materials and more discussion concerning polymers"--
Includes bibliographical references and index.
Keywords: Materials